Robotic Versus Laparoscopic Distal Pancreatectomy for Pancreatic Ductal Adenocarcinoma: A Systematic Review and Meta-Analysis - Feng, Qingbo; Jiang, Chuang; Feng, Xuping; Du, Yan; Liao, Wenwei; Jin, Hongyu; Liao, Mingheng; Zeng, Yong; Huang, Jiwei (Frontiers in Oncology, 2021)
Abstract Background: Robotic distal pancreatectomy (RDP) and laparoscopic distal pancreatectomy (LDP) are the two principal minimally invasive surgical approaches for patients with pancreatic body and tail adenocarcinoma. The use of RDP and LDP for pancreatic ductal adenocarcinoma (PDAC) remains controversial and which one can provide a better R0 rate is not clear. Method: A comprehensive search for studies that compared robotic versus laparoscopic distal pancreatectomy for PDAC published until July 31, 2021, was conducted. Data on perioperative outcomes and oncologic outcomes (R0-resection and lymph node dissection) were subjected to meta-analysis. PubMed, Cochrane Central Register, Web of Science and EMBASE were searched based on a defined search strategy to identify eligible studies before July 2021. Results: Six retrospective studies comprising 572 patients (152 and 420 patients underwent RDP and LDP) were included. The present meta-analysis showed that there were no significant differences in operative time, tumor size, and lymph node dissection between RDP and LDP group. Nevertheless, compared with the LDP group, results seem to demonstrate a possibility in higher R0 resection rate (p＜0.0001). Conclusions: This systematic review and meta-analysis suggest that RDP is a technically and oncologically safe and feasible approach for selected PDAC patients. Large randomized and controlled prospective studies are needed to confirm this data.